TEACHING VOCABULARY AND GRAMMAR WITH THE HELP OF SOME APPROACHES - Safarova Dildora; Abdugofur Khayitboyev (TADQIQOTLAR, 2025)
Annotation: This article explores the essential role of vocabulary and grammar in language acquisition and investigates effective teaching methods for both areas. The study compares explicit and contextual approaches to teaching vocabulary, as well as inductive and deductive strategies for grammar instruction. It also outlines practical techniques to help students develop a rich lexical resource and advanced grammatical accuracy. The goal is to inform language teachers about adaptable strategies that enhance students’ communicative competence.